Effectiveness of an exercise and nutrition intervention for older adults with mild cognitive impairment: an open-label double-arm clinical trial - Noguchi-Shinohara, Moeko; Yokoyama, Kunihiko; Komatsu, Junji; Masuda, Kazumi; Kouno, Mitsunobu; Yoshita, Mitsuhiro; Ono, Kenjiro (Frontiers in Aging Neuroscience, 2025)
BackgroundWe examined the efficacy of physical exercise with nutritional lectures in preventing cognitive decline among older adults.MethodsThis study included individuals aged ≥65 years who had no dementia. The intervention group underwent a physical exercise training program once a week and attended nutritional lectures once a month for 5 months. Baseline and 12-month cognitive assessments using the MCI Screen (MCIS) to measure memory performance were completed by individuals in the intervention (n = 76) and nonparticipant (n = 36) groups. The primary endpoint was changes in the memory performance index (MPI) scores of the MCIS.ResultsThe MPI score significantly increased by 1.8 in the intervention group and significantly decreased by 1.2 in the nonparticipant groups (p = 0.049).DiscussionMemory declines gradually overtime as a normal process of aging. Therefore, the decline of MPI score in the nonparticipant group is a natural change, however interestingly, the MPI scores improved in the intervention group, suggesting that the physical exercise with nutritional lectures may prevent memory function. Our results also suggest that through physical exercises and nutritional lectures, older adults might have developed exercise habits that increased their muscle weight which might have improved their cognitive function. A 5-month intervention of our physical exercise training program with nutritional lectures for older adults without dementia can improve their memory performance, especially individuals with 60s and 70s and with mild cognitive impairment.